Relasi Wajib Pajak Usaha Mikro Kecil Dan Menengah Ditinjau Dari Efektivitas Hukum Terhadap Kepatuhan Pelaporan Pajak Penghasilan Final Di Kota Batam - Jaya, Dedi (P3M dan Jurusan Syariah dan Ekonomi Bisnis Islam STAIN Sultan Abdurrahman Kepulauan Riau, 2024)
Micro, Small and Medium Enterprises (MSMEs) are becoming a lively business, as is the growth of MSMEs in Batam City which is very rapid, the economic movement of MSMEs also influences state income, but the awareness and knowledge of business actors about taxes is still very low even though they have facilitated by the Government, even though the role of taxes is so important for the country's development and common welfare. This can be seen from several factors that influence it, including law enforcement factors, facilities and infrastructure, society and culture which are the causes of problems and which influence MSME taxpayers in reporting their taxes. Therefore, this research aims to add insight to MSME actors regarding information on the implementation of tax payment obligations, and instill the importance of taxes for the state and provide solutions to several factors that become obstacles or influence people in paying their taxes.